Effect of diclofenac rectal suppository on pain relief after medio lateral episiotomy- a placebo controlled trial - Shah, Seiqa; Bhat, Shakura; Ahmad, Abida; Waheed, Arfat (Asian Journal of Medical Research, 2017)
Objective: To assess the effectiveness of Diclofenac rectal suppository for perineal pain relief after medio-lateral episiotomy. Methods: 100 pregnant women aged 20-35 years with gestational age 39-41 weeks were enrolled for this study and randomly allocated into 2 groups of 50 each to receive 100mg of diclofenac suppository or placebo suppository following medio-lateral episiotomy. Postoperative perineal pain was monitored using pain intensity scale and questionnaire which is scored as 0 = no pain, 1 = mild pain, 2 = discomforting pain, 3 = distressing pain, 4 = horrible pain and 5 = excruciating pain at 24hrs and 48hrs after child birth. Results: Demographic comparison was insignificant between the diclofenac and placebo groups. Patients in the diclofenac group showed significant (p-value 0.022) relief from perineal pain at rest and at movement at 24 hours post-partum when compared with placebo group; the difference being less at 48 hours. Additional analgesia at discharge was required by 21(42%) and 34(68%) patients in diclofenac and placebo groups respectively. Conclusion: The present study suggested that diclofenac has significant analgesic role in reducing perineal pain especially at 24hours after administration.